Advantages of the Rasch Model for Analysis and Interpretation of Attitudes: the Case of the Benevolent Sexism Subscale - Zamora Araya, José Andrey (2018)
This paper describes how the use of Rasch Analysis (RA), compared with the Classical Test Theory (CTT) and other Item Response Theory (IRT) approaches, could enhance the study and interpretation of attitudinal scales. This is illustrated with data from 197 students from the University of Costa Rica who answered the Benevolent Sexism (BS) Scale (Glick & Fiske, 1996). Besides providing estimations of the measure’s specific accuracy at different levels of the construct, the RA, thanks to the person versus item map, allowed us to generate respondents’ profiles describing particular aspects of the construct and according to their estimated scores in the scale. The analysis indicated that construct categories for participants with scores between [-0.30, 0.5] in the logit scale are the most accurately represented, with more items covering this interval, and reflecting the three aspects of the scale described by the theory. On the other hand, results showed less measurement accuracy for a considerable number of respondents with lower scores, suggesting the need for the development of additional items for that level of the scale. These evidences are discussed in light of the benefits of using the RA for the understanding and interpretations of respondents’ scores in attitudinal scales, according to the underlying theory.